Computational micromechanics of the effect of fibre misalignment on the longitudinal compression and shear properties of UD fibre-reinforced plastics. (15th September 2020) - Sebaey, T.A.; Catalanotti, G.; Lopes, C.S.; O'Dowd, N.
Abstract: In this paper, 3D representative volume elements (RVEs) of UD carbon/epoxy composites are generated, taking into consideration a realistic misalignment of the fibres. To construct the RVE, a 2D distribution of the fibre sections is considered and then extruded in the longitudinal direction. Experimental measurements to the misalignments are modelled by perturbing the positions of the control points defined on the centreline of each fibre, representing the fibre path as a Bézier curve. The individual fibres are considered as linear elastic orthotropic whereas, the matrix is modelled as isotropic using a damage-plasticity model. The fibre/matrix interface is modelled using a cohesive formulation law. The IM7/8552 material was simulated using three loading conditions: longitudinal compression, longitudinal shear, and transverse shear. The results show clear correlation between fibre misalignment and compression strength, and stiffness. For shear loading, no effect is recorded. Under the three loading conditions, the predicted material properties and damage propagation are in agreement with the data available in the literature.